Keberadaan Iman dan Kemanusiaan dalam Pemaknaan Filosofis Gabriel Marcel dan Kristianitas Gensler - Putra, Merry Christian (Proceedings of The National Conference on Indonesian Philosophy and Theology, 2023)
This writing explores the intrinsic relationship between religion and humanity, highlighting the thoughts of philosopher Gabriel Marcel on the importance of intersubjective relations in achieving ontological unity. Through Marcel's lens, human existence is described as an existential journey that requires self-understanding and understanding of others, where love and togetherness become bridges to self-fulfillment and existential awareness. Furthermore, based on the phenomena of Islamophobia and religious intolerance, the principle of "humanity above religion" becomes the main topic of discussion. Through the concept of the Law of Love in Christianity and Gensler's thoughts on the relationship between faith and morality, this writing emphasizes the need for cooperation and understanding among religions in a pluralistic society. It is also emphasized that acceptance and humanity cannot be separated; they both need each other to create a balance that allows individuals to become whole persons. Through this analysis, this writing seeks to offer a new perspective in understanding and addressing issues of intolerance and religious conflict, emphasizing the importance of transcendent human values above religious differences.  ABSTRAKTulisan ini menggali hubungan intrinsik antara keberagamaan dan kemanusiaan, dengan menyoroti pemikiran filsuf Gabriel Marcel tentang pentingnya relasi intersubjektif dalam mencapai kesatuan ontologis. Melalui lensa pemikiran Marcel, keberadaan manusia dijelaskan sebagai perjalanan eksistensial yang memerlukan pemahaman diri sendiri dan orang lain, di mana cinta dan kebersamaan menjadi jembatan menuju pemenuhan diri dan kesadaran eksistensial. Selain itu, tulisan ini didasarkan pula adanya fenomena Islamophobia dan intoleransi agama, maka prinsip “kemanusiaan di atas agama” menjadi pokok pembahasan yang diangkat. Melalui konsep pemikiran akan Hukum Kasih dalam Kristianitas dan pemikiran Gensler tentang hubungan antara iman dan moralitas, tulisan ini menekankan perlunya kerjasama dan pengertian antaragama dalam masyarakat pluralistik. Ditekankan pula bahwa keberimanan dan kemanusiaan tidak dapat dipisahkan; keduanya saling membutuhkan untuk menciptakan keseimbangan yang memungkinkan individu menjadi pribadi yang utuh. Melalui analisis ini, tulisan ini berupaya menawarkan perspektif baru dalam memahami dan mengatasi permasalahan intoleransi dan konflik agama, dengan menekankan pentingnya nilai kemanusiaan yang transenden di atas perbedaan agama.